Stepping down therapy for well-controlled mild asthma: an experience from University Medical Center at Ho Chi Minh City - Lam, Nguyen-Ho (Asia Pac Allergy, 2021)
BACKGROUND: Stepping down treatment for well-controlled mild asthma is challenging to clinicians. The step-down strategy using regularly-intermittent low-dose inhaled corticosteroid has been applied at the University Medical Center (UMC) of Ho Chi Minh City, called as “UMC” approach. OBJECTIVE: This study aimed to evaluate the efficiency of UMC step-down strategy in well- controlled mild asthma. METHODS: A real-world retrospective descriptive study was conducted at UMC from 2009 to 2018. All asthmatic patients (age ≥ 12) who received step-down therapy using this UMC approach were evaluated. RESULTS: Among 2,072 asthma patients to be treated with UMC step-down strategy, only 112 subjects were eligible. The median age was 38.5 years and female was 62.5%. Most patients at their initial presentation were indicated step 4 treatment (87.5%). The controller medications before initiation of UMC treatment included fluticasone propionate 125 μg once-daily, salmeterol/fluticasone propionate 25/125 μg once-daily, and formoterol/budesonide 4.5/160 μg once-daily. After being treated with the UMC approach, the rates of well-controlled asthma ranged from 67.6% to 91.1%. During 1 year with UMC treatment, pulmonary function remained stable and only 7 subjects (6.3%) developed exacerbation. CONCLUSION: The UMC step-down treatment for well-controlled mild asthma was relatively efficient in maintaining asthma control, stabilization of pulmonary function, and reducing risk of severe exacerbation.